Sufism and Mental Health: Application of Sufism Principles in Mental Well-Being - Afiani, Vivia Zahira; Haririe, Muhammad Ruhiyat (Journal of Sufism and Psychotherapy, 2024)
Spirituality in the Islamic religion, known as Sufism, offers principles that can be implemented to support mental health and overall mental well-being. This study examines the relationship between the principles of Sufism and mental health, and how their application can have a positive impact on mental well-being. The main principles of Sufism discussed include reading the Al-Qur'an (while understanding its meaning), prayer, associating with pious people, fasting, and dhikr and prayer. The Qur'an is the first and most important therapy for the welfare of the soul, so that it can provide peace of mind and reduce anxiety and restlessness. Prayer is a manifestation of repentance which can relieve all the burdens of life which can cause stress, tension and anxiety. Associating with righteous people can be a spiritual medicine for illnesses. Fasting teaches us to refrain from all bad things. Meanwhile, dhikr provides peace of mind through closeness to God. Through in-depth literature studies and analysis of Sufism's teachings, this research reveals that these principles have the potential to reduce stress, anxiety and depression, as well as increase resilience and happiness. Apart from that, these principles can also treat mental disorders, both worldly and spiritual. This research highlights the importance of integrating Sufism principles in counseling and therapy practice, as well as providing practical recommendations for individuals and society to apply these teachings in everyday life.